If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+16x+5=0
We simplify the equation to the form, which is simple to understand
3x+16x+5=0
We move all terms containing x to the left and all other terms to the right.
+3x+16x=0-5
We simplify left and right side of the equation.
+19x=-5
We divide both sides of the equation by 19 to get x.
x=-0.263157894737
| A^2+4a=45 | | -1x^2+7x+9=0 | | 4x+8=2(x+12) | | 2y-3=11 | | 1x^2-6x=7 | | Y=14X+7 | | (x+3)(x+3)-(x-1)(x+5)(x+3)+(x-5)(x+5)3=0 | | 2x^2+16+28=0 | | -10x^11y^11Z^13+4x^11y^11z^13= | | 6c-14=-2 | | (-4y^8z^4)(-x^3y^3z^3)(x^8z^6)= | | 10x-126=4x-12 | | 102-4x=14x+16 | | 12x-28=56 | | 9a+5=13 | | r+10=3 | | 3x+11=-97-9x | | 192=0.5t | | 3x+11=23 | | 106-3x=3x+22 | | -5(-2x^4y^2z^2)(-x^3y^9Z^3)(x^4z^8)= | | r-6=-11 | | 95m+m=565 | | p-10=-20 | | 60t=45(t+2) | | r-3=-10 | | 4x^4+27x^2-81=0 | | [5y-1.3]=2.7 | | (-8x^2y^2z)(5xyz)= | | 136-2x=25x+19 | | n+10=4 | | 13-8x=65-22x |